If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5x + 4 = -6 Reorder the terms: 4 + 6x + -5x = -6 Combine like terms: 6x + -5x = 1x 4 + 1x = -6 Solving 4 + 1x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 1x = -6 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = -6 + -4 1x = -6 + -4 Combine like terms: -6 + -4 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| w=3(x+y+z)y | | v-16=-6 | | 3c-36=-3c-12 | | 9y-5y+10=-19 | | 0.33-4=-8 | | 2=5w+12 | | 5s-21=39 | | m=6(p+q)q | | 3(x+2)=-5-2(x-4) | | 25-39=11 | | 6X+19X-7=5(5X+5) | | -0.75=-0.6+s | | -2.4x=-2.88 | | 5x+28(x-2)=406 | | x-5x=7x-9x-x | | X+0.375=-1.75 | | -328=-56b+7 | | -5+4r=-5r+4r | | 19-13p=-5-17p | | 0.5+0.5j=0 | | ln(5X+1)=4.5 | | 3x+12=7x-22 | | x+3(x-3)=91 | | 2x=-16+4y | | 3x-66=9x | | 1+k=3k-1 | | -0.6+y=-0.33 | | -28=v-18 | | 20+18x-2=21x | | X-9.2=-4.55 | | 4=p-1 | | X-1.25=3.5 |